2015
DOI: 10.1016/j.eurpolymj.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Poly(epsilon caprolactone)/clay nanocomposites via host–guest chemistry

Abstract: a b s t r a c tCyclodextrin-modified montmorillonite (MMT-CD) has been prepared from commercial montmorillonite clay (Closite 30B) containing two hydroxyl groups by reacting succinic anhydride through esterification. Poly(epsilon caprolactone) (PCL)/clay nanocomposites are prepared by host-guest chemistry between MMT-CD as host and PCL, hydrophobic polymer as guest. The structures of the intermediates and final nanocomposite are investigated in detail by FT-IR XRD, TEM, DSC and TGA measurements. The intercalat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The observed individual clay layers (highlighted by black circle and labeled as ( e ) were well dispersed (delaminated), whereas large intercalated tactoids (highlighted by black circle and labeled as ( i ) in the polymer matrix were clearly seen in both samples. Due to the high loading degree or limited mobility of PMATRIF chains within the layers, the small stacks of intercalated MMT layers were occurred . Consequently, combined XRD and TEM results confirmed that all nanocomposites had a mixed morphology, in which partially exfoliated/intercalated MMT layers in the PMATRIF matrix.…”
Section: Resultsmentioning
confidence: 87%
“…The observed individual clay layers (highlighted by black circle and labeled as ( e ) were well dispersed (delaminated), whereas large intercalated tactoids (highlighted by black circle and labeled as ( i ) in the polymer matrix were clearly seen in both samples. Due to the high loading degree or limited mobility of PMATRIF chains within the layers, the small stacks of intercalated MMT layers were occurred . Consequently, combined XRD and TEM results confirmed that all nanocomposites had a mixed morphology, in which partially exfoliated/intercalated MMT layers in the PMATRIF matrix.…”
Section: Resultsmentioning
confidence: 87%
“…Nanocomposites of biodegradable aliphatic polyesters with layered silicates are considered very promising for a wide range of applications spanning from the packaging to the biomedical and agricultural sectors . Nanocomposites of nanoclays with poly( ϵ ‐caprolactone), polyhydroxybutyrate, poly(butylene succinate), polylactide as well as copolyesters of butylene adipate such as maleated poly[(butylene adipate)‐ co ‐terephthalate] 2 or poly[(butylene succinate)‐ co ‐adipate] and its blend with polylactide have been investigated. Low‐molecular‐weight PBA has been used as a building block in combination with poly(3‐hydroxybutyrate)‐diol for the synthesis of a polyurethane nanocomposite by one‐step solution polymerization with 1,6‐hexamethylene diisocyanate .…”
Section: Introductionmentioning
confidence: 99%
“…The combination of organic and inorganic structures within a single material at nanoscopic level is one of the most effective approaches for producing new class of hybrids materials with advanced properties. A wide range of nanoparticles such as: clays, carbon nanotubes, graphites, polyhedral oligomeric silsesquioxane and metal oxides are currently available and used for prepared these systems [1]. These new compounds have been increasingly used in biomedical, pharmaceutical and cosmetics applications, presenting many advantages compared with individual polymers or other pharmaceutical excipients, such as: controlled drug release, targeted drug delivery, improved mechanical properties and stability [2] [3].…”
Section: Introductionmentioning
confidence: 99%
“…The clays are the most studied inorganic nanoparticles because of their abundance, price and well-known intercalation process. Depending on the interfacial interactions and mode of dispersion of the polymer and clay layers, three distinct morphologies can be obtained: unintercalated or microcomposite, intercalated or flocculated and exfoliated or delaminated [1]. Furthermore, clays nanoparticles have been highlighted in the pharmaceutical area, since they are widely used in conventional pharmaceutical dosage forms both as excipients and active agents.…”
Section: Introductionmentioning
confidence: 99%